2016
DOI: 10.1037/fam0000229
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-origin parents’ differential treatment and siblings’ adjustment from adolescence to young adulthood.

Abstract: Parents’ differential treatment is a common family dynamic that has been linked to youth’s well-being in childhood and adolescence in European American families. Much less is known, however, about this family process in other ethnic groups. We examined the longitudinal associations between parents’ differential treatment (PDT) and both depressive symptoms and risky behaviors of Mexican-origin sibling pairs from early adolescence through young adulthood. We also tested the moderating roles of cultural orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
2
25
1
Order By: Relevance
“…Another study suggested that adolescents reported higher levels of maternal and paternal differential parenting in terms of both support and negative interaction at times they also reported more internalizing behavior (Shanahan et al 2008). However, this was not replicated by Padilla et al (2016), who found that only increases in maternal differential treatment in support were related to concurrent increases in internalizing behavior within families, but not paternal differential support or maternal/paternal differential negative interaction. Thus, only a handful of longitudinal studies have assessed concurrent associations between differential parenting and externalizing and internalizing behavior within families.…”
Section: Differential Parentingmentioning
confidence: 88%
See 2 more Smart Citations
“…Another study suggested that adolescents reported higher levels of maternal and paternal differential parenting in terms of both support and negative interaction at times they also reported more internalizing behavior (Shanahan et al 2008). However, this was not replicated by Padilla et al (2016), who found that only increases in maternal differential treatment in support were related to concurrent increases in internalizing behavior within families, but not paternal differential support or maternal/paternal differential negative interaction. Thus, only a handful of longitudinal studies have assessed concurrent associations between differential parenting and externalizing and internalizing behavior within families.…”
Section: Differential Parentingmentioning
confidence: 88%
“…Three studies assessed concurrent within-family links of differential parenting (i.e., differential treatment of siblings). The parental treatment was different in respect to negative interaction and support (Padilla et al 2016;Shanahan et al 2008) or control (Richmond et al 2005) and these differences (rather than the absolute levels of parenting) were linked to adolescent adaptation on a macro timescale. Two studies that focused on the link with externalizing behavior suggested that increases in differential parenting co-varied with simultaneous increases in adolescents' externalizing behavior at the within-family level (Richmond et al 2005).…”
Section: Differential Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the sample was European American, twoparent families, limiting the generalizability of findings. Among families in other cultural contexts, for example, PDT can have different implications depending on youth's cultural orientations (Padilla, McHale, Updegraff, & Umaña-Taylor, 2016), and thus research on sibling experiences in other cultural groups is an important direction. Third, our dependent variable was dichotomous given the importance of college graduation for well-being throughout adult life (IOM & NRC, 2015), but future research should assess more fine-grained differences between siblings' education achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Differential treatment from parents is a common phenomenon in family dynamics, and it has been linked to the disruption of well-being during adolescence and youth [20]. in adolescent descendants of Mexicans, the perception of low parental warmth in comparison to their siblings' is associated with greater risk behaviours and depressive symptoms [20].…”
mentioning
confidence: 99%